Serum High Sensitive C - reactive protein in Male Smokers of Bangladesh - Jahan, Shamima; Akhter, Qaz Shamima (Journal of Bangladesh Society of Physiologist, 2015)
Background: Smoking may cause systemic inflammation, and high level of serum high sensitive Creactive protein may be found in smoker as an indicator of inflammation. Objective: To assess the serum high sensitive C - reactive protein level in male smokers of Bangladesh. Methods: The present cross sectional study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka between July 2013 and June 2014. Hundred apparently healthy male regular cigarette smokers aged 20 to 40 years who smokes at least 5 sticks of cigarette per day for the last 5 years were included as study group. They were further divided in to 5-10 years, 11-15 years, 16-20 years and 1-10 cigarette sticks, 11- 20 cigarette sticks, more than 20 cigarette sticks/day depending on the duration of smoking and also according to consumption of number of sticks/day respectively. Age matched 100 apparently healthy male nonsmokers were included for control. To assess their inflammatory status, serum hs-CRP level was estimated by particles enhanced immunonephelometry using BN Systems in the Department of Microbiology & Immunology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. In addition, BMI and blood pressure were measured by standard method to observe their association with smoking. Results: The mean serum hs-CRP level was significantly higher in male smokers than that of non smokers which was progressively increased with duration of smoking and number of cigarette sticks consumed per day. Again, mean BMI was significantly lower and diastolic blood pressure was significantly higher in male smokers than those of non smokers. Conclusion: The result of this study can be concluded that serum hs-CRP level progressively increases with duration of smoking and number of cigarette sticks consumed per day in male smokers. Bangladesh Soc Physiol. 2015, June; 10(1): 36-40